Muscle injury, impaired muscle function and insulin resistance in Chromogranin A-knockout mice. Issue 2 (February 2017) - Tang, Kechun; Pasqua, Teresa; Biswas, Angshuman; Mahata, Sumana; Tang, Jennifer; Tang, Alisa; Bandyopadhyay, Gautam K; Sinha-Hikim, Amiya P; Chi, Nai-Wen; Webster, Nicholas J G; Corti, Angelo; Mahata, Sushil K
Abstract : Chromogranin A (CgA) is widely expressed in endocrine and neuroendocrine tissues as well as in the central nervous system. We observed CgA expression (mRNA and protein) in the gastrocnemius (GAS) muscle and found that performance of CgA-deficient Chga -KO mice in treadmill exercise was impaired. Supplementation with CgA in Chga -KO mice restored exercise ability suggesting a novel role for endogenous CgA in skeletal muscle function. Chga -KO mice display (i) lack of exercise-induced stimulation of pAKT, pTBC1D1 and phospho-p38 kinase signaling, (ii) loss of GAS muscle mass, (iii) extensive formation of tubular aggregates (TA), (iv) disorganized cristae architecture in mitochondria, (v) increased expression of the inflammatory cytokines Tnfα, Il6 and Ifnγ, and fibrosis. The impaired maximum running speed and endurance in the treadmill exercise in Chga -KO mice correlated with decreased glucose uptake and glycolysis, defects in glucose oxidation and decreased mitochondrial cytochrome C oxidase activity. The lack of adaptation to endurance training correlated with the lack of stimulation of p38MAPK that is known to mediate the response to tissue damage. As CgA sorts proteins to the regulated secretory pathway, we speculate that lack of CgA could cause misfolding of membrane proteins inducing aggregation of sarcoplasmic reticulum (SR) membranes and formation of tubular aggregates that is observed in Chga -KO mice. In conclusion, CgA deficiency renders the muscle energy deficient, impairs performance in treadmill exercise and prevents regeneration after exercise-induced tissue damage.